2021
DOI: 10.21775/cimb.041.381
|View full text |Cite
|
Sign up to set email alerts
|

Oncolytic HSV Vectors and Anti-Tumor Immunity

Abstract: The therapeutic promise of oncolytic viruses (OVs) rests on their ability to both selectively kill tumor cells and induce anti-tumor immunity. The potential of tumors to be recognized and eliminated by an effective anti-tumor immune caister.com/cimb 381 Curr. Issues Mol. Biol. Vol. 41 Oncolytic HSV Vectors Glorioso response has been spurred on by the discovery that immune checkpoint inhibition can overcome tumor-specific cytotoxic T cell (CTL) exhaustion and provide durable responses in multiple tumor indicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 282 publications
0
11
0
1
Order By: Relevance
“…imunidade inata e à apresentação de antigénio favorecida pelas moléculas MHC classe I (Glorioso et al, 2021). As células CD8 T produzem a sua expansão clonal em gânglios linfáticos e baço, migrando subsequentemente para locais de inflamação guiados por quimiocinas (Aldrak et al, 2021).…”
Section: Indução Da Actividade Imunitária Adaptativaunclassified
“…imunidade inata e à apresentação de antigénio favorecida pelas moléculas MHC classe I (Glorioso et al, 2021). As células CD8 T produzem a sua expansão clonal em gânglios linfáticos e baço, migrando subsequentemente para locais de inflamação guiados por quimiocinas (Aldrak et al, 2021).…”
Section: Indução Da Actividade Imunitária Adaptativaunclassified
“…Chemokines and cytokines regulate the trafficking and infiltration of immune cells into the TME. Studies have shown that the infection of OVs elicits potent type I interferon responses (115,116), which can stimulate the production of T cell recruiting chemokines. Inflammatory factors such as tumor necrosis factor (TNF) and interleukin-1b (IL-1b) can also be induced by OVs, which in turn upregulate the expression of selectin on endothelial cells and provide an important signal for T cell infiltration (117)(118)(119).…”
Section: The Combination Of Tumor Vaccines and Oncolytic Virusesmentioning
confidence: 99%
“…Considerable effort has gone into creating safe and effective herpes simplex virus (HSV) vectors that demonstrate tumor cell–specific oncolysis (oHSV). 1 The oHSV vector talimogene laherparepvec (T-VEC) showed durable responses in 16.3% of melanoma patients following direct intratumoral delivery, 2 and was approved by the US Food and Drug Administration in 2015 for the treatment of solid tumors. 3 T-VEC is attenuated by the deletion of the genes encoding γ34.5 and ICP47, and expresses the human granulocyte-macrophage colony-stimulating factor gene to stimulate an immune response.…”
Section: Introductionmentioning
confidence: 99%